2021
DOI: 10.18844/cjes.v16i6.6536
|View full text |Cite
|
Sign up to set email alerts
|

The role of discipline "Olympic Education" in training specialists of "Physical Culture and Sport" in Kazakhstan

Abstract: Kazakhstan makes a significant contribution to the development of physical culture and sports in the Olympic games and as such, there is an urgent direction to study the prospects for the development of the educational services market and conduct research on consumers of educational services. The purpose of our study was to study and analyze the activities for the organization and implementation of work, related to the massive introduction of the ideas of Olympism and Olympic education in the daily life of bot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 3 publications
0
1
0
Order By: Relevance
“…Olympic education can strengthen PE. Bakhtiyarova et al [66] suggest that the Olympic education movement will increase the motivation of the younger generation to engage in PE and sports. The study participants have suggested asking the Olympians to motivate students.…”
Section: Theme 5 Leveraging the Relationship Between The Olympics And Pementioning
confidence: 99%
“…Olympic education can strengthen PE. Bakhtiyarova et al [66] suggest that the Olympic education movement will increase the motivation of the younger generation to engage in PE and sports. The study participants have suggested asking the Olympians to motivate students.…”
Section: Theme 5 Leveraging the Relationship Between The Olympics And Pementioning
confidence: 99%
“…Olympic education is an area that needs to be researched and studied in detail. The educational value of the Olympic movement is also invaluable, as it is a way of integrating Ukrainian culture, experience and scientific knowledge, which contributes to the formation of a generally developed, educated person, in particular, a teacher in the field of physical education and sports (Bakhtiyarova et al, 2020;Galan et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…It is known that while technology continues to advance in education in the world, many areas such as social life and education are trying to adapt to the technological change process in education (Shagataeva et al, 2021), and some adapt to the information and communication technology of this time as soon as they are born. It is known that those who learn to use these technologies later are called 'digital immigrants' (Bakhtiyarova et al, 2021). It is known that the perspectives and thought patterns of today's secondary school students, i.e., digital natives, differ from those of digital immigrants (Elmira et al, 2021).…”
Section: Introductionmentioning
confidence: 99%